Histochemical detection and comparison of apoptotic cells in the gingival epithelium using hematoxylin and eosin and methyl green-pyronin: A pilot study - Aarati Nayak; Anita Raikar; Vijaylaxmi Kotrashetti; Ramakant Nayak; Sumedha Shree; Soumya Kambali (Wolters Kluwer Medknow Publications, 2016)
Background: Apoptosis plays a critical role in the regulation of inflammation and host immune response. It helps in tissue homeostasis and a disturbance in this is often associated with disease. The use of histochemical stains like hematoxylin and eosin (H and E) and methyl green-pyronin (MGP) can provide a simple and cost-effective method for the detection of apoptotic cells. Aim: Study intended to analyze the expression of apoptosis in the gingival epithelium of healthy subjects and in patients with chronic periodontitis, using H and E and MGP. It is also proposed to correlate the apoptotic index (AI) of healthy individuals and those with chronic periodontitis. Materials and Methods: Twenty gingival biopsies were harvested from which ten samples were of healthy subjects and ten subjects who suffered from chronic periodontitis. Apoptotic cells were analyzed using MGP and H and E under light microscopy. Results: Apoptotic cells were identified at ×100 magnification and AI was calculated. Apoptotic cells were easily distinguishable in MGP stained sections when compared to those stained using H and E. Moreover, apoptotic cell count was higher in chronic periodontitis. Statistical analyses were done by Tukey's multiple post hoc procedure. Conclusion: The study reveals that MGP staining can be used in a routine basic laboratory set up as one of the cost-effective methods for the detection of apoptotic cells.